Developing independent musicians in middle school band through the components of playing and chamber music - Postlewaite, Andreia C. (Kansas State University, 2022)
The goal of this project was to guide middle school band students to understand then utilize the components of playing in order to create realistic goals that met them at their level of musicianship. Students were introduced to five components of playing: time, tone, playing in tune, with good technique, and with blend and balance. Students were given the opportunity to then form their own chamber groups where they would set goals derived from the components. Before students participated in activities to focus on each component, they were asked to independently define either one or more of the components using their own words and musical experiences in writing. Activities took place at the start of a rehearsal and that focused on one component per activity. For time, I provided students with a sight-reading rhythm excerpt for them to perform on one note. With this same excerpt they then completed a written activity breaking down time signatures and utilizing a counting system. Students also participated in a phrase-based rhythmic audiation activity. I created a tuning rotation activity for our flute and saxophone players where they started tuning from mouthpiece, to neck/headjoint to horn. To learn about tone, we had a variety of discussions in class about what the sound quality or character would look or feel like within a given musical work we were rehearsing. Students were also asked to independently explore and describe the tone of two different professional musicians performing on their instrument of study using their own words. I created sight-singing and audiation activities to engage students’ in first internalizing pitch through their singing voice then through their instruments. Technique was reinforced throughout full ensemble rehearsals with intentional questions to remind students to observe and correct within their sections. Students took an active role in blend and balance by listening back to recordings of themselves and commenting on who they heard more or less of and what strategy they might use to adjust accordingly. I have been motivated to try strategies that allow for a focused balance towards the multitude of tasks demanded of an instrumental music teacher. The informative yet practical delivery and guidance of instrumental music education text, examples, organized lectures, feedback, and assistance from Dr. Wimmer, Dr. Gardner, and Dr. Tracz’s coursework helped me gain new tools and a new perspective on how to approach an instrumental music program. I was highly motivated to start to explore and maintain practical strategies to balance the work of research, application, reflection, and modification of activities that challenged both myself and my students. Through the inspirational and at times brutally honest reflection processes in Dr. Tracz’s and Dr. Payne’s classes, I have experienced that successful leadership is an ongoing process that is not necessarily about being in control. It involves consistency, thoughtful planning, taking risks, failing, succeeding, engaging in a variety of research, applying research in a manner that is realistic and motivational, and being transparent about the importance of all goals that our music programs set out to achieve.
Keywords: Middle school; Musicianship; Developing